IMPLIKASI PERAN DAN FUNGSI PENGAWASAN PERBANKAN MENURUT PERATURAN OTORITAS JASA KEUANGAN NOMOR 5 TAHUN 2024 - Arsa Adika Pramana; Kusuma, Wahyu Rangga; Dihyan Arga Perdana; M Fikry Aimmar Rabbani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Banking supervision is an important element in maintaining financial system stability and supporting sustainable economic growth. As an independent supervisory institution, the Financial Services Authority (OJK) plays a strategic role in regulating and supervising the financial services sector, including banking, based on Law Number 21 of 2011. OJK Regulation Number 5 of 2024 exists as a response to global economic dynamics, technological advances, and new challenges such as cybercrime and customer data protection. This regulation forces strengthening governance, risk management and digital innovation in the banking sector. This study uses normative juridical research methods with a qualitative approach to analyze the legal framework and the influence of POJK 5/2024 on the banking sector. The analysis results show that POJK 5/2024 strengthens the risk-based supervision system (Risk-Based Supervision) and bank governance, as well as encouraging the digitalization of banking services. These regulations also increase transparency and consumer protection, although they pose challenges, especially for small banks that face capital and technology limitations. Through this analysis, it is hoped that adaptive supervision can strengthen the competitiveness of Indonesian banking, increase public trust, and support national financial stability. This research provides recommendations for improving coordination between institutions, as well as ensuring that the implementation of regulations is effective in order to achieve the goals of a fair and sustainable financial system.